Between Linguistic Geography and Structural Linguistics: The development of Eugenio Coseriu’s variational approach in the 1950s - Jensen, Viggo Bank; Cigana, Lorenzo (Scandinavian Studies in Language, 2023)
In this paper, we follow the development of Coseriu’s conceptual tools for variational linguistics during the 1950s. Our starting point is Pisani’s notion of “isogloss”, which Coseriu initially regarded as a core idea for his own approach and yet progressively abandoned in favour of the more structuralist-oriented notion of “functional language”, adopted in the wake of Louis Hjelmslev’s framework, through Leiv Flydal’s mediation. Finally, we speculate about the reasons and the implications of Coseriu’s failing to acknowledge Uriel Weinreich as an important source for variational linguistics.